Implementasi Metode Work Sampling Guna Mengukur Produktivitas Penjaga Kasir di McDonald's Harapan Indah, Bekasi Barat - Seri Hendra; Hendy Tannady (Universitas Bunda Mulia, 2017)
McDonald's is one of the many brands of fast food restaurant franchise that stands in various cities in Indonesia. In the present study, researchers had implemented the method of work sampling to one of the workers in charge of maintaining a cashier at a McDonald's restaurant that stands in the Harapan Indah, Bekasi Barat. The purpose of this study was to measure the level of productivity, normal time and standard time of each element of the work of employees who served in the front line at the fast food restaurant. According to the results of the calculation and analysis of the data, the level of productivity of the worker at McDonald's cashier is 88.86%, followed by the normal time and standard time by 21.06 seconds and 23.4 seconds. This figure has been demonstrated that the level of productivity and the speed of service from a McDonald's cashier worker is good.Keywords: Work Sampling, Productivity, Normal Time, Standard Time.